Dialog Interreligius Perspektif Sayid Qutub dan Peran Pemerintah dalam Meningkatkan Toleransi di Indonesia - Fachruli Isra Rukmana; Sri Kurniati Yuzar (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The dynamics of tolerance in Indonesia have always been a major concern for a pluralistic society. Social conflicts often use religion as an excuse to worsen the situation, so religion becomes an issue that always causes conflict in society. Therefore, the views of Sayid Qutub and Christianity in the Gospel about tolerance can be used as an idea to promote perfect tolerance in Indonesia. This research formulates three problems, first, the comparison of the concept of tolerance from the perspective of Sayid Qutub and Christianity in the Gospel. Second, what things should be considered by the government in promoting tolerance in Indonesia according to Sayid Qutub's view? Third, how interfaith dialog affects the progress of tolerance according to Sayid Qutub in Indonesia. This research uses library research with an interpretative analysis approach. The results of this study show that the interreligious dialog initiated by Sayid Qutub in Fi Zhilalil Qur'an can be a solution to promote peace among religious communities in Indonesia. Unfortunately, the government pays little attention to interfaith dialog, which has been infiltrated by personal and political interests, as well as intolerant doctrines carried out by religious leaders. Therefore, the government should immediately address and establish interfaith dialog to promote tolerance in Indonesia.